116k views
0 votes
Y=x^2-3x-6

x+y=2


Help 50 Points!!! Show Work

User Tuss
by
5.4k points

2 Answers

1 vote

Answer:

x=-2 and y=4 or x=4 and y=-2

Explanation:

put the value for y (first equation) in for the y in the second equation so it is x+x^2-3x-6=2

simplify

x^2-2x-8=0

factor and you get (x-4)(x+2)=0

(x-4)=0. x=4

x+2=0 x=-2

now insert that back into x+y=2

and you get

y=-2

y=4

respecitvely

Hope this helps :)

User Bolizhou
by
6.4k points
1 vote
x + y = 2 —> y = 2 - x
insert to first equation
2-x=x^2-3x-6
x^2 - 3x - 6 - 2 + x = 0
x^2 - 2x - 8 = 0
(x-4)(x+2) = 0
x = 4 or x = -2
User Adejones
by
6.3k points